Kepemimpinan Spiritual dalam Lembaga Pendidikan: Analisis Maqasid Syariah - Millah, Nur Ita A’ini Qudwatal; Far’ia (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
Leadership in an educational institution is one of the determining factors in the success of aneducational institution. Through a good system and pattern of leadership, educationalinstitutions will be able to know where they want to go and reach clearly. Spiritual intelligenceis needed for a leader to lead an educational institution, especially Islamic educationalinstitutions. In the scope of leadership based on spiritual values, the orientation of all itsactivities is as a manifestation of worship and a means of devotion to God. Therefore, thejournal discusses the concept of spiritual leadership in Islamic educational institutions Maqashid Sharia perspective in terms of dharuriyyat starting from the side of hifdz al-din, hifdzal-nafs, hifdz al-aql, hifdz al-nasl and hifdz al-mal and its implementation in the Da'wahManagement Study Program of UIN Sunan Kalijaga Yogyakarta. This research uses descriptivequalitative study methods. Data collection techniques using observation, interviews anddocumentation. The results showed that the head of the department in this study program hada main program in education and training as part of the development of spiritual leadership.Through this case, the head of the department and the lecturer do not simply abort theadministrative obligations, namely to carry out the learning process, but also as a means ofdevotion to God. In addition, spiritual leadership is demonstrated through exemplary efforts tothe characteristics of the Prophet, namely siddiq, amanah, tabligh, and fathanah as well asvarious forms of policies implemented by the Chair of the Department aiming to achieve mutualbenefit.